Inattentive Attention-Deficit/Hyperactivity Disorder, Stimulant Medication, and Weight Loss in a 15-Year-Old Girl: Are We Enabling the Development of an Eating Disorder?. Issue 1 (February 2017) - Iyer, Sai; Kumar, Maya; Reiff, Michael I.; Stein, Martin T.
Abstract : CASE: Nicole is a 15-year-old girl presenting to the Developmental Behavioral Pediatrics Clinic with symptoms of the inattentive type of Attention-Deficit/Hyperactivity Disorder (ADHD) and declining school performance over the last year. She expressed frustration over her inability to concentrate on schoolwork. Assuming that her poor grades were secondary to lack of effort, her parents withdrew privileges. Nicole became increasingly depressed. She stopped participating in activities, she previously enjoyed, and her parents reported that she stopped singing in the shower. After talking to a cousin with ADHD, Nicole concluded that she had ADHD as well. She asked her parents to arrange for an evaluation. Nicole met DSM-5 criteria for the diagnosis of inattentive ADHD and was started on a stimulant medication (mixed amphetamine salts). She had symptoms of a coexisting depression, although she did not meet criteria for diagnosis of a depressive disorder. At a 3-week follow-up visit, she showed improvement in targeted ADHD symptoms; homework was now easier and her grades improved. At a 2-month follow-up, Nicole's weight dropped from 53 kg (47th percentile) prestimulant treatment to 49 kg (31st percentile). She reported appetite suppression after taking the stimulant but did not feel that her eating habits had changed significantly. Her father reported that she had a preference for junk food and snacks. Nicole did not enjoy exercising and did not participate in extracurricular sports. She weighed herself several times a day, as she was worried about losing too much weight. Nicole's mood continued to be low, despite the fact that her grades improved, and her parents were more understanding of her challenges. She was otherwise healthy and reported regular menstrual cycles. Nicole requested an increase in the dose of stimulant medication for greater improvement in concentration during homework and in school. Her pediatric clinician was concerned about the possibility of an eating disorder in addition to depression. She asked herself, "Are we treating inattentive ADHD effectively or are we enabling an eating disorder?"